Tourenplanung mit alternativen Lieferperioden und Teillieferungen - Breier, Heiko (KIT Scientific Publishing, 2014)
This book examines the Vehicle-Routing-Problem with split-deliveries and alternative delivery periods (SDVRPA). It is solved with a Branch-and-Price-Algorithm. When alternative delivery periods and split-deliveries are employed, freight forwarders get a wider scope for planning and can therefore plan more efficient routes. Even with few alternative delivery periods, which allow vehicles to be used more efficiently, substantial savings can be achieved.
German
Keywords: Column-Generation; SDVRPAVehicle-Routing-Problem; Alternative Periods; SDVRPA; Tourenplanung; Teillieferungen; Branch-Price-and-Cut; Alternative Perioden; Split-Deliveries